Production and Characterization of Activated Carbon from Dashen Brewery Gondar Spent Label as Precursor (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this work is to identify a precursor from brewery industry waste to produce activated carbon and the same could be used for the treatment of brewery inlet water. Among the wastes generated in the industry, it was found that spent label paper has good potential as precursor since it has good cellulose content. One more attractive feature of this spent label is that it is in-house generated waste and is available at free of cost. The activated carbon was prepared by following chemical activation process. The various activation agents like potassium chloride, phosphoric acid, potassium hydroxide and Zinc chloride were used as the chemical activation agent and their effect on Iodine value and the yield and was studied. A methodical study of the effect of concentration of activation agent, impregnation time, activation temperature and activation time on the iodine value and the yield % during the production of activated carbon from spent label was studied. The prepared activated carbon was characterized by measuring the iodine number and yield percentage. The apparent density of the chemically activated carbons was examined and found to be 0.43 g/ml. Also, the adsorption power of the prepared activated carbon was checked by using methylene blue. During the test it was visually observed that the color intensity reduced enormously, which is an indication that the product was successfully activated. The optimum conditions for the production of activated carbon are a 2 N concentration of zinc chloride activating agent with 20 h of impregnation time and at a activation temperature of 600oC for an activation time of 1 h gave rise to an iodine number of 734.7 mg/g, which is relatively a good number.